Some Issues Regarding the Europeanization of National Criminal Law - Mitreva, Petya (Research Papers, 2023)
The subject of the article is the Europeanization of the criminal law of the Member States of the European Union. The author’s opinion is that EU criminal law influences not only the specific part, but also the institutions of the general part of criminal law. This raises the question of bridging the differences between national criminal law systems in order to achieve the European Union's common policy on combating particularly serious crime with a cross-border dimension.
Keywords: European union criminal law; Europeanisation; Especially serious crime with a cross-border dimension